Plankton Diversity as Mirrored by Silver Carp (Hypophthalmichthys molitrix) Gut Contents in Rupa Lake, Pokhara, Nepal - Ghising, Srishti (Nepalese Journal of Aquaculture and Fisheries, 2023)
A study was conducted in Rupa Lake from February to April of 2023 to investigate plankton diversity and gut content in silver carp (Hypophthalmichthys molitrix) in the lake. Samples were collected from 25 locations using a <75 μm mesh plankton net. The samples were preserved in Lugol’s solution, and quantitatively analyzed using a Sedgewick Rafter Counting Chamber. Environmental parameters like temperature, pH, dissolved oxygen, and water transparency were examined. Silver carp samples were collected from daily catch of the lake and gut sample was preserved in 70% ethanol. The gut contents were analysed qualitatively using microscope. Altogether 28 genera, 13 belonging to phytoplankton and 15 belonging to zooplankton were recorded in the lake. The phytoplankton belonged to 4 groups with Chlorophyceae, Bacillariophyceae, Cyanophyceae, Zygnematophyceae based on dominance. The zooplankton belonged to 3 groups with Rotifera, Copepoda, Cladocera based on dominance. The highest number of phytoplankton and zooplankton were recorded in the deeper region, and lowest in the outlet area. The dominant phytoplankton in the gut of silver carp was Chlorophyceae, Cyanophyceae and Bacillariophyceae. The dominant zooplankton in the gut of silver carp was Cladocera, Copepoda and Rotifera. Diet of silver carp mostly corresponded with phytoplankton and zooplankton available in the Lake.